DESIGN AND ANALYASIS A BROADBAND PRINTED-DIPOLE ANTENNA FOR 4G/5G MOBILE SMARTPHONE - HACHIM, ABEER KAMIL; KADHIM , MOHAMMED ABOUD; HAMID, HAMOOD SHEHAB (Journal of Duhok University, 2023)
Wireless communications are of great importance in our lives, especially mobile phones, and based on this importance, we propose in this research an antenna . It works on the medium frequencies of both 4G/5G technologies . The proposed antenna has dimension (17.7×7) mm (length x width ) made of copper and a substrate FR-4 the finished thickness is 1.67mm .This design is connected in the port it equals 1mm by using microstrip line method . The ground and substrate layers are a symmetrical rectangle. The patch is also simple, as it represents a strip of copper that surrounds the rectangle on three sides. It has only one line in the middle with a length of 8.5mm and a width of 1mm. The design is simple as it does not have any openings. Small size and small thickness makes it suitable for the size of modern mobiles. The micorstrio patch antenna is was designed by using CST studio -2019 and manufactured via the ProtoMat-100 machine. The antenna operates at range frequencies (2.35-3.74) GHz and .It has resonance frequency 2.9 GHz at return loss of -54 dB.